Users' emotional responses and perceived product quality towards sustainable design - Alli, Hassan; Mohd Rashid, Mohamad Saiful Sazwan (Universiti Putra Malaysia Press, 2019)
Emotion of a product has influenced the user interaction and enhanced the value and quality. Also, the quality performs as a cognitive response influencing the user in distinguishing the quality of a product. Nowadays, many product designers have trouble in interpreting potential meanings and perceiving the quality of a product in product development process that should be contributed for sustainable design. The strength of this study emphases not only in identifying and verifying the variable of user’s emotional responses and perceptions in the product quality, but also focuses in developing a new theory of sustainable product design method towards sustainable design. A survey with the involvement of the end users (consumer product) was conducted in this study. The results recognized certain variables of user’s emotional responses and perceptions towards the product quality, which is a significant contribution towards product sustainability and as well as increasing its success in the market. In addition, a new theories of Sustainable Product Design Method (SPDM) has been introduced.